UJI EFEK EPITELISASI EKSTRAK DAUN PALA (Myristica fragrans Houtt.) PADA TIKUS JANTAN - Azhary, Nursyahidah; Wati, Aulia; Herman, Hendra; Kosman, Rachmat (As-Syifaa Jurnal Farmasi, 2024)
Burns are damage or loss of tissue that occurs due to exposure to a heat source such as fire, hot liquids or fats, steam, radiation, electric current, or chemicals. Purpose of the research This is to determine the effect and effective dose of the ethanol extract of nutmeg leaves (Myristica fragrans Houtt.) in accelerating the epithelialization process in burn wounds. This study used 15 animals mice were divided into five treatment groups, namely negative control group (Na-CMC), positive control group (lanaeloid), and three test groups that received the dosed extract different: 200 mg/kgBB, 400 mg/kgBB, and 600 mg/kgBB. Burns are induced using a plate heat at 100ºC for 2 seconds on the rat's back. Therapy given topically twice a day for 21 days. Wound area measurements were carried out on days 1, 3, 5, 7, 14, and 21. The research results were statistically tested using the One Way Anova test with the Bonferroni post hoc test. Results The research showed that the positive control group was not significantly different from the test extract group. Based on the research results, it can be concluded that the ethanol extract of nutmeg leaves (Myristica fragrans Houtt.) has an epithelialization effect on mice with an effective dose of 600 mg/kgBB